Foreign direct investment and economic growth: empirical evidence from Russian regions - Svetlana Ledyaeva; Mikael Linden (Bank of Finland, Institute for Economies in Transition (BOFIT), 2006)
Barro and Sala-I-Martin empirical framework of neoclassical Solow-Swan model is specified to determine the FDI impact on per capita growth in 74 Russian regions during period of 1996-2003.The Arellano-Bond GMM-DIFF methodology, developed for dynamic panel data models, is used in estimations.Results imply that in general FDI (or related investment components) do not contribute significantly to economic growth in Russia in the analyzed period. Regional growth in 1996-2003 is explained by the initial level of region's economic development, the 1998 financial crisis, domestic investments, and exports.However some evidence of positive aggregate FDI effects in higher-income regions is relevant.Another interesting result is that natural resource availability seems to be growth-inducing in rich regions, while in poor regions it is not significant.We also found convergence between poor and rich regions in Russia.However FDI seems not to play any significant role in the recent growth convergence process among Russian regions.
URN:NBN:fi:bof-201408072060
Keywords: E22; F21; P27; 330; Foreign Direct Investment (FDI); Russian regional economy; and economic growth